2013
DOI: 10.1080/10408398.2012.697497
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review about the Health Risk Assessment of PAHs and Their Metabolites in Foods

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a family of toxicants that are ubiquitous in the environment. These contaminants generate considerable interest, because some of them are highly carcinogenic in laboratory animals and have been implicated in breast, lung, and colon cancers in humans. Dietary intake of PAHs constitutes a major source of exposure in humans. Factors affecting the accumulation of PAHs in the diet, their absorption following ingestion, and strategies to assess risk from exposure to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 201 publications
0
51
0
1
Order By: Relevance
“…Moreover, if one can avoid the direct contact of high temperature during grilling (i.e., cooking on direct flame), it also reduces the formation of PAHs (Faradian et al, 2011;Chen and Lin, 1997). The use of minimum heat and keeping food to the farthest point of heating, if combined, can lower their production more efficiently (Rey-Salgueiro et al, 2008;Yebra-Pimentel et al, 2013).…”
Section: Cooking Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, if one can avoid the direct contact of high temperature during grilling (i.e., cooking on direct flame), it also reduces the formation of PAHs (Faradian et al, 2011;Chen and Lin, 1997). The use of minimum heat and keeping food to the farthest point of heating, if combined, can lower their production more efficiently (Rey-Salgueiro et al, 2008;Yebra-Pimentel et al, 2013).…”
Section: Cooking Methodsmentioning
confidence: 97%
“…The same contaminated oil was reported to be used in the bakery industry for the preparation of various cookies and biscuits (Yebra-Pimentel et al, 2013). Drying of oil seeds at higher temperature tends to promote the generation of PAH.…”
Section: Cooking Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are a large number of nutrients and compounds in the diet that suppress cancer. 44 Such biologically active compounds are known to influence cell proliferation and cell death, 45,46 as well as carcinogen activation and detoxification. 47 The remainder of this review will discuss results from studies where attempts were made to counteract the impact of meat by including other dietary components that may suppress colon carcinogenesis (Table 3).…”
Section: Mechanistic Evidence -Protection Conferred By Other Dietary mentioning
confidence: 99%
“…Lipid peroxidation: Pimentel et al [36] reported increased levels of lipid peroxidation (based on MDA levels) under high temperature and pCO 2 . Correspondingly lipid peroxidation (also based on MDA levels) increased at low pH and high pCO 2 in the present study.…”
Section: Glutathione -S -Transferase Activitymentioning
confidence: 99%